The Way of the Shaman and the Revival of Spiritual Healing in Post-Soviet Kazakhstan and Kyrgyzstan - Penkala-Gawęcka, Danuta (International Society for Academic Research on Shamanism, 2014)
Despite many years of Soviet rule in Central Asia, traditional medical beliefs and practices were not eradicated and their revival has been noticeable in the independent republics of Kazakhstan and Kyrgyzstan. Religious and magical healing, including shamanism, are important parts of this renewed tradition. This article, based on extensive fieldwork conducted in Almaty, Kazakhstan, and its vicinity between 1996 and 2000, and in Bishkek, the capital of Kyrgyzstan, between 2011 and 2013, examines the revival of healing, including shamanism. It focuses on the way of a shaman and of other spiritual healers—the process of recognizing the call of spirits and gaining skills and power, peculiarities of their spiritual development and its social conditions. Additionally, I present this kind of healing in the context of complementary medicine in Kazakhstan and Kyrgyzstan, which, generally, has achieved a strong position in these countries. I discuss complex factors that influence its popularity and official recognition, as well as observable fluctuations in the attitude of the authorities to non-biomedical methods of treatment. On the basis of my analysis I conclude that tradition plays a crucial role in the revival of spiritual healing.
Keywords: Shamanism; Shaman; Healing; Kazakhstan; Kyrgyzstan